Integrating Local Wisdom into Modern Education to Promote Sustainable and Holistic Learning Practices - Lucas Daniel Anderson (PT. Islamic Research Publisher, 2024)
This study explores the integration of local wisdom into modern education to promote sustainable and holistic learning practices. The primary objective is to examine how indigenous knowledge can be systematically incorporated into contemporary curricula to enhance students’ cognitive, social, and ethical development while fostering environmental awareness and cultural identity. Employing a qualitative multi-case study design, the research involved curriculum analysis, semi-structured interviews with educators and community leaders, and classroom observations in various educational settings. Data were analyzed thematically to identify patterns, challenges, and effective strategies in integrating local wisdom into teaching and learning processes. The findings reveal that embedding local wisdom in modern education contributes significantly to holistic learning outcomes. Culturally relevant content, project-based and experiential learning, and active engagement with local communities were identified as effective strategies. Students exposed to such integrative practices demonstrated higher levels of critical thinking, ethical reasoning, collaboration skills, and sensitivity toward sustainability issues. However, the study also highlights several challenges, including limited teacher preparedness, insufficient institutional support, and gaps in policy alignment, which may hinder the full realization of integrative educational approaches. The study contributes to educational theory and practice by offering a framework for systematically incorporating local wisdom into contemporary curricula, emphasizing the alignment of cultural knowledge with sustainable development goals. It provides practical implications for curriculum designers, educators, and policymakers seeking to foster inclusive, culturally grounded, and sustainable learning environments. By bridging traditional knowledge with modern educational paradigms, this research underscores the potential of local wisdom as a transformative resource for creating resilient, reflective, and socially responsible learners.